Evaluation of Some Biochemical Parameters and Hormones In Patients with Acute Myeloid Leukemia in Iraq - Jumaah, Hind Mahmood; Yenzeel, Jabbar H.; Mehdi, Mohammad G. (Iraqi Journal of Science, 2021)
The effect of myeloid leukemia, especially cute myeloid leukemia (AML), has been widely noticed on the parameters of liver and kidney functions and the levels of certain hormones. This study aimed to evaluate a number of biochemical parameters of liver and kidney functions and hormones in Iraqi subjects with newly diagnosed acute myeloid leukemia. Eighty newly diagnosed AML adult patients (40 males and 40 females) and forty healthy individuals (20 males and 20 females) with an age range of 16-75 years were involved in this study during their attendance at the Hematology Department of Baghdad Teaching Hospital/ Medical city in Baghdad province from March 2019 to February 2020. Blood samples were collected from all subjects for the determination of serum levels of the parameters of liver function parameters., kidney function , lactate dehydrogenase (LDH), and Erythropoietin (EPO). The results showed that the serum levels of liver function parameters (alanine aminotransferase (ALT), aspartate aminotransferase (AST), and alkaline phosphatase (ALP) had highly significant increases (p< 0.01) in AML patients (85.87±2.49 , 53.93±1.76, 150.87±7.04 U/L, respectively) as compared to the control (30.58 ±2.04, 22.89 ±0.97, 75.51 ±2.12 U/L, respectively ). Also, the level of kidney function parameters (blood urea, creatinine and uric acid) showed highly significant increases (p< 0.01) in AML patients (58.82 ±1.49, 1.831 ±0.05, 8.34 ±0.15 mg/dl, respectively) as compared to the control (31.10 ±1.03, 0.850 ±0.02, 4.81 ±0.14 mg/dl, respectively). In addition, the level of LDH showed a highly significant increase (p< 0.01) in the patients with AML (657.72 ±80.76 U/L) as compared to the control (166.05 ±6.15 U/L). Moreover, the level of EPO showed a highly significant increase (p<0.01) in the patients with AML (11763.80 ±329.46 pg/ml ) as compared to the control (316.94 ±34.42 pg/ml).